Reconstructing Indonesia's Tourism Law: A Strategic Framework for Sustainable and Inclusive Tourism Governance - Mafrudoh, Lut; Rahmanita, Myrza; Jaya, Lalu Aswadi; Wahjono, Budi; Wahjono, Faisal (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This article critically examines the urgency to revise Indonesia’s Law No. 10 of 2009 on Tourism to address current challenges in the tourism sector. The law, though once progressive, is now outdated amid rapid digital transformation, the need for sustainability, and increased community participation. Through a normative legal and comparative approach, this study identifies critical gaps, such as the lack of digital governance, weak legal protection for tourism workers and MSMEs, and the absence of crisis mitigation mechanisms. The findings recommend integrating principles of sustainable development, digital transparency, and inclusive governance into the revised legal framework. Furthermore, the revision should recognize community-based tourism (CBT), strengthen the role of local governments and BUMDs, and provide legal certainty in post-disaster tourism recovery. A well-formulated legal foundation is essential to ensure that tourism becomes not only a driver of economic growth but also a tool for environmental conservation and social equity. This study contributes to the discourse on tourism legislation reform and supports a more adaptive and inclusive legal framework for Indonesia’s tourism sector.